2021
DOI: 10.1007/s11469-021-00552-9
|View full text |Cite
|
Sign up to set email alerts
|

Unique Associations of Revised-Reinforcement Sensitivity Theory Constructs with Social Anxiety

Abstract: Revised reinforcement sensitivity theory (r-RST) is a major neuropsychological theory of motivation, emotion and personality. We report the results of a study that examined the unique relationships of the r-RST constructs with two forms of anxiety: social interaction social performance. Five hundred and seventy-twoA adults completed the Reinforcement Sensitivity Theory of Personality Questionnaire (RST-PQ) alongside measures of social interaction anxiety and social performance anxiety. Regression results revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 41 publications
(60 reference statements)
3
12
1
Order By: Relevance
“…Multiple regression indicated positive relationships concerning how BIS and total FFFS scores relate to both SIAS and SPS scores, and a negative relationship between FFFS defensive fight scores and SIAS but not SPS scores. In these regression analyses SIAS but not SPS scores were related to reduced BAS reward interest, and both SIAS and SPS scores were related to reduced BAS goal drive persistence scores (Gomez et al, 2021). It is notable here that in both sets of analyses SIAS and SPS scores were differentially related to the FFFS dimension of defensive fight.…”
Section: Social Anxiety and Reinforcement Sensitivitymentioning
confidence: 58%
See 2 more Smart Citations
“…Multiple regression indicated positive relationships concerning how BIS and total FFFS scores relate to both SIAS and SPS scores, and a negative relationship between FFFS defensive fight scores and SIAS but not SPS scores. In these regression analyses SIAS but not SPS scores were related to reduced BAS reward interest, and both SIAS and SPS scores were related to reduced BAS goal drive persistence scores (Gomez et al, 2021). It is notable here that in both sets of analyses SIAS and SPS scores were differentially related to the FFFS dimension of defensive fight.…”
Section: Social Anxiety and Reinforcement Sensitivitymentioning
confidence: 58%
“…We use the rRST-Q (Reuter, Cooper, Smillie, Markett, & Montag, 2015), which is a contemporary measure of rRST that was not administered in the above studies. Based upon a synthesis of the results reported by Gomez et al (2021) and Kramer and Rodriguez (2018) we predict that zero-order corelations will show that both SIAS and SPS will be positively correlated with BIS, FFFS-flight, and FFFSfreeze scores. Based on Kramer and Rodriguez (2018), who used a unitary revised BAS scale, we also predict that both SIAS and SPS will share a negative relationship with BAS scores.…”
Section: The Present Studymentioning
confidence: 96%
See 1 more Smart Citation
“…Self-report studies have reported zero-order correlations showing that both trait social interaction anxiety and trait social phobia are positively correlated with BIS sensitivity, FFFS-flight/freeze sensitivity, and negatively correlated with BAS sensitivity and FFFS-fight sensitivity (e.g., du Rocher & Warfield, 2022;Gomez et al, 2022). Although a comparison of multiple regression analyses across different studies can show inconsistent results concerning which reinforcement sensitivity is the most prominent predictor of SIAS or SPS scores (e.g., du Rocher & Warfield, 2022; Gomez et al, 2022;Kramer & Rodriguez, 2018), these analyses do suggest that the rRST measures can explain a moderate amount of variance in both SIAS scores, and SPS scores. Future studies might test the relationship between self-reported BIS, BAS and FFFS sensitivity and the happy face RT advantage, as well as the RT congruency effect in the emotional face flanker task.…”
Section: Discussionmentioning
confidence: 99%
“…There is therefore an important gap in the literature as these studies did not differentiate the cognitive correlates of trait social interaction anxiety (fearfulness and avoidance of situations where social interaction with other people is a requirement) from those of trait social phobia / social observation anxiety (fearfulness and avoidance of situations where observation & Clarke, 1998). The SPS scale (which measures the fear of social scrutiny; Mattick & Clarke, 1998) is sometimes retitled as a measure of social observation anxiety (e.g., Gomez et al, 2022;Kramer & Rodriguez, 2018).…”
Section: The Present Studymentioning
confidence: 99%